Rethinking development economics (London Anthem Press, 2003)
This book addresses key issues in development economics, from macroeconomics, finance and governance to trade, industry, agriculture and poverty. Bringing together some of the foremost names in the field, this comprehensive and timely collection constitutes a critical staging post in the future of development economics.
Includes bibliographical references.
Keywords: Development economics